IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM UPAYA PENINGKATAN MUTU PEMBELAJARAN MUTU PEMBELAJARAN MATA PELAJARAN AGAMA ISLAM DI SMPN 1 BAMBEL - RIDWAN, RIDWAN (UNISAN JURNAL, 2025)
School Based Management (SBM). It is a system consisting of elements and therefore the results of educational activities in schools are the collective result of all school elements. In this way of thinking, all school elements must understand the concept of SBM, why and how SBM is organized. Schools implementing SBM must make a school development plan. School development plans generally include the formulation of the school's vision, mission, goals and implementation strategy. Meanwhile, the school's annual work plan generally includes identifying school goals (school situational goals), selecting school functions needed to achieve the identified goals, SWOT analysis, problem-solving steps, and preparing an annual school work plan and program. The following describes briefly the formulation of the vision, mission, goals and objectives of the school (school situational goals). The purpose of this study is to find out the implementation of school-based management in an effort to improve the quality of teaching the Pendidikan Agama Islam SMP N 1 Bambel in the 2024/2025 academic year. This type of research is evaluation research using qualitative research methods. According to Sugiyono, evaluation research is research that aims to compare an event, activity and product with established standards and programs, so that evaluation research functions to explain phenomena. Based on the results of observational interviews, and documentation regarding the implementation of school- based management in the implementation of school-based management in an effort to improve the quality of learning Aqidah Akhlak SMP N 1 Bambel for the 2024/2025 academic year at the planning stage is quite good.